Avascular Necrosis of the Femoral Head in Patients with Antiphospholipid Syndrome: A Case Series - Paschalis Evangelidis; Eleni Gavriilaki; Nikolaos Kotsiou; Zacharo Ntova; Panagiotis Kalmoukos; Theodosia Papadopoulou; Sofia Chissan; Sofia Vakalopoulou (Hematology Reports)
Background/Objectives: Antiphospholipid syndrome (APS) is a systemic autoimmune disease characterized by thrombosis or obstetric complications and the laboratory detection of antiphospholipid antibodies. Although vascular thrombosis is the main manifestation of the disease, other rarer complications have also been described. Avascular necrosis (AN) is considered a rare manifestation of APS. The aim of our case series is to study patients with APS and AN. Methods: A retrospective study was performed on 80 patients diagnosed with APS. Results: AN was observed in 3 patients out of 80 diagnosed with APS. AN of the femoral head was observed in all cases. Case (1): A 54-year-old woman presented due to multiple ischemic infarctions in the brain, as detected in magnetic resonance imaging of the brain, Raynaud’s phenomenon, and AN of the femoral head. In laboratory testing, a prolongation of activated partial thromboplastin time was recorded. A heterozygous mutation was also found in the gene MTHFR C677T, and the patients was positive for lupus anticoagulant (LA). The patient was given clopidogrel and acenocoumarol. Case (2): A 52-year-old man was diagnosed with APS, based on the clinical presentation (stroke) and positivity for LA and anti-β2GPI (anti-β2 glycoprotein I antibody). In his medical history, episodes of vertigo and an episode of AN of the femoral head 2 years ago were described. Case (3): A woman aged 43 years presented due to AN of the femoral head. Due to suspected APS, immunological testing was performed, and positivity for LA and IgM anticardiolipin antibodies was detected. She was treated with acenocoumarol. Conclusions: AN is a rare clinical manifestation of APS, which may precede the diagnosis of APS for many years.